2011
DOI: 10.2174/138920211798120853
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Alterations in Poorly Differentiated and Undifferentiated Thyroid Carcinomas

Abstract: Thyroid gland presents a wide spectrum of tumours derived from follicular cells that range from well differentiated, papillary and follicular carcinoma (PTC and FTC, respectively), usually carrying a good prognosis, to the clinically aggressive, poorly differentiated (PDTC) and undifferentiated thyroid carcinoma (UTC).It is usually accepted that PDTC and UTC occur either de novo or progress from a pre-existing well differentiated carcinoma through a multistep process of genetic and epigenetic changes that lead… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
68
0
7

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 74 publications
(78 citation statements)
references
References 94 publications
3
68
0
7
Order By: Relevance
“…No mutations were detected in medullary thyroid carcinomas, as described by Killela et al 3 , nor in normal thyroid and benign lesions, such as goitre, adenomas or thyroiditis; this finding fits with previous studies that reported telomerase expression in malignant lesions and not in normal tissue or hyperplastic lesions 8,9 . TERT mutations were associated with clinicopathological features (older age, increased tumour size and a b male gender), but, after histotype stratification, these associations were only maintained in cPTC.…”
Section: Resultssupporting
confidence: 91%
“…No mutations were detected in medullary thyroid carcinomas, as described by Killela et al 3 , nor in normal thyroid and benign lesions, such as goitre, adenomas or thyroiditis; this finding fits with previous studies that reported telomerase expression in malignant lesions and not in normal tissue or hyperplastic lesions 8,9 . TERT mutations were associated with clinicopathological features (older age, increased tumour size and a b male gender), but, after histotype stratification, these associations were only maintained in cPTC.…”
Section: Resultssupporting
confidence: 91%
“…In line with this, telomerase activity in normal thyroid samples is almost absent, being detected in less than 7 % of cases [16,114]. On the other hand, telomerase activity was consistently reported in a specific population of thyroid cells-the solid cell nests (SCNs) which are considered to represent embryonic remnants of the ultimobranchial body [95,101].…”
Section: Telomerase Promoter Mutations In Thyroid Carcinomasmentioning
confidence: 92%
“…In PDTCs, beta-catenin (CTNNB1), p53, and BRAF V600E mutations can be also present. Although the most common oncogene alteration in ATCs are p53 point mutations, BRAF V600E , PIK3CA, PTEN, IDH1, and ALK mutations have all been reported in these aggressive thyroid tumors, in which, unlike in other hystotypes, it is not uncommon to have multiple genetic alterations in the same tumoral tissue (Eng et al 1996, Smallridge et al 2009, Soares et al 2011.…”
Section: :4mentioning
confidence: 99%
“…Despite the many genetic alterations that have been described for thyroid cancer and the most recent efforts to find other activated oncogenes, approximately 5-10% of PTCs, 50-60% of MTCs, and 10% of ATCs and PDTCs are still negative for all known genetic abnormalities (Soares et al 2011, Giordano et al 2014, Ji et al 2015.…”
Section: :4mentioning
confidence: 99%